2021
DOI: 10.3390/pharmaceutics13081274
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Omeprazole on the Dissolution Processes of pH-Dependent Magnetic Tablets Assessed by Pharmacomagnetography

Abstract: Pharmacomagnetography involves the simultaneous assessment of solid dosage forms (SDFs) in the human gastrointestinal (GI) tract and the drug plasmatic concentration, using a biomagnetic technique and pharmacokinetics analysis. This multi-instrumental approach helps the evaluation, as GI variables can interfere with the drug delivery processes. This study aimed to employ pharmacomagnetography to evaluate the influence of omeprazole on the drug release and absorption of metronidazole administered orally in magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Our group has extensive knowledge in drug delivery studies and gastroenterology assessments in animals and humans using the ACB methodology, focusing on assessing solid dosage forms in the through images [ 17 , 35 – 38 ]. Our group also has studied the effects of pathologies, surgeries, and disturbed physiological states of the gastrointestinal transit in rats through images [ 39 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has extensive knowledge in drug delivery studies and gastroenterology assessments in animals and humans using the ACB methodology, focusing on assessing solid dosage forms in the through images [ 17 , 35 – 38 ]. Our group also has studied the effects of pathologies, surgeries, and disturbed physiological states of the gastrointestinal transit in rats through images [ 39 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Floating lag time (FLT), gastric retention time (GRT), and orocaecal transit time (OCTT) were determined by scanning gastric projections in different regions [ 58 , 60 ]. By collecting data on magnetic field deformation intensity over time and registering it in a data matrix, images corresponding to the tablet’s position at specific times can be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the procedure, volunteers received a standard lunch (Perdigão ® lasagna with Del Valle ® orange juice, Perdigão, Brazil). Floating lag time (FLT), gastric retention time (GRT), and orocaecal transit time (OCTT) were determined by scanning gastric projections in different regions [58,60]. By Floating lag time (FLT), gastric retention time (GRT), and orocaecal transit time (OCTT) were determined by scanning gastric projections in different regions [58,60].…”
Section: In Vivo Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies showed the potential of the ACB system to perform quantitative ex vivo biodistribution studies of MNPs employing organs and cells samples with both position and volume fixed (1D quantitative signals) [15,16,19,20]. Therefore, it is desired to both assess the ACB system's abilities for imaging and quantitative analysis, and to increase its spatial resolution, to perform MNP quantitative imaging of tablets, organs, and anatomical structures, which can be used in pharmaceutical and physiological studies [12,16,17,21,22]. Such an achievement can create new possibilities of ACB applications in biomedical studies involving MNPs.…”
Section: Introductionmentioning
confidence: 99%